Controlled, Low‐Temperature Nanogap Propagation in Graphene Using Femtosecond Laser Patterning. Issue 31 (3rd July 2018) - Maurice, Ange; Bodelot, Laurence; Tay, Beng Kang; Lebental, Bérengère
Abstract: Graphene nanogap systems are promising research tools for molecular electronics, memories, and nanodevices. Here, a way to control the propagation of nanogaps in monolayer graphene during electroburning is demonstrated. A tightly focused femtosecond laser beam is used to induce defects in graphene according to selected patterns. It is shown that, contrary to the pristine graphene devices where nanogap position and shape are uncontrolled, the nanogaps in prepatterned devices propagate along the defect line created by the femtosecond laser. Using passive voltage contrast combined with atomic force microscopy, the reproducibility of the process with a 92% success rate over 26 devices is confirmed. Coupling in situ infrared thermography and finite element analysis yields a real‐time estimation of the device temperature during electrical loading. The controlled nanogap formation occurs well below 50 °C when the defect density is high enough. In the perspective of graphene‐based circuit fabrication, the availability of a cold electroburning process is critical to preserve the full circuit from thermal damage. Abstract : The propagation of graphene nanogaps is controlled by local femtosecond laser irradiation. After electroburning, the nanogap propagation is shown to systematically follow the laser pattern containing a high defect density. Finite element analysis coupled with infrared thermography shows that the higher the defect density, the lower the electroburning temperature.